CoCl2, a mimic of hypoxia, induces formation of polyploid giant cells with stem characteristics in colon cancer. - Laura M Lopez-Sánchez (PLoS ONE, 2014)
The induction of polyploidy is considered the reproductive end of cells, but there is evidence that polyploid giant cancer cells (PGCCs) contribute to cell repopulation during tumor relapse. However, the role of these cells in the development, progression and response to therapy in colon cancer remains undefined. Therefore, the main objective of this study was to investigate the generation of PGCCs in colon cancer cells and identify mechanisms of formation. Treatment of HCT-116 and Caco-2 colon cancer cells with the hypoxia mimic CoCl2 induced the formation of cells with larger cell and nuclear size (PGCCs), while the cells with normal morphology were selectively eliminated. Cytometric analysis showed that CoCl2 treatment induced G2 cell cycle arrest and the generation of a polyploid cell subpopulation with increased cellular DNA content. Polyploidy of hypoxia-induced PGCCs was confirmed by FISH analysis. Furthermore, CoCl2 treatment effectively induced the stabilization of HIF-1α, the differential expression of a truncated form of p53 (p47) and decreased levels of cyclin D1, indicating molecular mechanisms associated with cell cycle arrest at G2. Generation of PGCCs also contributed to expansion of a cell subpopulation with cancer stem cells (CSCs) characteristics, as indicated by colonosphere formation assays, and enhanced chemoresistance to 5-fluorouracil and oxaliplatin. In conclusion, the pharmacological induction of hypoxia in colon cancer cells causes the formation of PGCCs, the expansion of a cell subpopulation with CSC characteristics and chemoresistance. The molecular mechanisms involved, including the stabilization of HIF-1 α, the involvement of p53/p47 isoform and cell cycle arrest at G2, suggest novel targets to prevent tumor relapse and treatment failure in colon cancer.